IMPLEMENTASI KUOTA 30 PERSEN KETERWAKILAN PEREMPUAN PADA PEMILIHAN LEGISLATIF DI KOTA JAYAPURA PERIODE TAHUN 2019-2024 - Herlina Nura Linthin; Renida Jozelina Torobi (Universitas Cenderawasih, 2022)
General Election (Pemilu) are a medium for channeling democracy by providing opportunities for every citizen who has met the requirements to be elected as representatives of the people, both executive and legislative. The regulation regarding the mandatory 30 percent quota for female legislative candidates is one of the importained in a number of laws, namely Law number 7 of 2017 concerning elections and Law number 2 of 2011 concerning amendments to Law number 2 of 2008. The problem is how to implement, the inhibiting factors and the efforts made to fulfill the 30 percent quota of women’s representative elections in Jayapura city for the 2019-2024 period.The type of research used is descriptive research with qualitative methods, namely this research is designed with qualitative methods. The research was was constructed in Jayapura City with the following respondents. Elements of the Regional People’s Representative Council (DPRD), Elements of the General Election Commission (KPU) Elements of the Party Carrying Women Legislative Candidates in Jayapura City. The results of the study that : first, policy efforts to make it happen have been carried out as optimally as possible; second, the role of women in p to politics is still considered as a complement to political activities in order fulfill the requirements of parties to participate in democratic parties, tend to do a lot of considerations and feel so influence the gait of women in democratic parties; third, It is necessary for women to be prepared to fulfill their knowledge, experience and struggle optimally, parties are expected to be committed to fulfilling the the quota for women’s representation, and the role of parties in encouraging women to fight more so that the quota of 30 percent of women’s representation in legislative elections can be fulfilled